Depth-dependent variations of dissolved organic matter composition and humification in a plateau lake using fluorescence spectroscopy. (June 2019) - Song, Fanhao; Wu, Fengchang; Feng, Weiying; Liu, Shasha; He, Jia; Li, Tingting; Zhang, Jin; Wu, Aiming; Amarasiriwardena, Dulasiri; Xing, Baoshan; Bai, Yingchen
Abstract: In aquatic systems, dissolved organic matter (DOM) plays an important role in regulating the reactivity and transport of environmental pollutants. Fluorescence excitation-emission matrix (EEM) analysis combined with fluorescence regional integration (FRI) and parallel factorial analysis (PARAFAC) were applied to investigate the composition, humification degree and depth-dependent variation of DOM in Lake Baihua, China. The results showed that humic-like materials with more than 60% of percentage fluorescence response ( P i, n ) were dominant in DOM. The molecular complexity and structural condensation of PARAFAC components showed the order of C1 (humic-like components) > C3 (protein-like components) > C4 (fulvic-like components) > C2 (fulvic-like components). The lower maximum fluorescence intensities ( F max ) of components in surface layers were attributed to photo-oxidation of DOM by radiation. With depths less than 16 m, the F max increases and decreases were attributed to accumulation of recalcitrant humic substances and microbial/abiotic degradation of particulate DOM, respectively. A combination of biological and humification indices could be used as indicators for distinguishing different degrees of humification and sources of DOM. DOM from Lake Baihua mainly originated from an aquatic bacterial source that consisted of an important/intermediate autochthonous component with a weak humic character. The fluorescence indices of P I, n / P II, n, P I+II+IV, n / P III+V, n, C2, C1/C2 and C2/(C3+C4) were more suitable to determine the humification degree. Stronger humic characters and higher humification degree for DOM were present at depths of 10–13 m. The fluorescence spectroscopy combined with fluorescence indices is convenient to investigate depth-dependent DOM characteristics and to assess water quality or pollution risk in lake systems. Graphical abstract: Image 1 Highlights: Depth-dependent variation of lake DOM were studied by fluorescence spectroscopy. Humic-like components show highest molecular complexity and structural condensation. Photo-/microbial degradation and accumulation were attributed to components changes. Evaluation of humification degree was developed based on various fluorescence indices.